2021
DOI: 10.21203/rs.3.rs-637392/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meditation-Induced Effects on Whole-Brain Structural and Effective Connectivity

Abstract: In the past decades, there has been a growing scientific interest in characterizing neural correlates of meditation training. Nonetheless, the mechanisms underlying meditation remain elusive. In the present work, we investigated meditation-related changes in structural and functional connectivities (SC and FC, respectively). For this purpose, we scanned experienced meditators and control (naive) subjects using magnetic resonance imaging (MRI) to acquire structural and functional data during two conditions, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Many previous studies have shown a relationship between mindfulness scores and functional connectivity of the lCEN and salience network, but not the rCEN [19,20]. A more recent study demonstrated that the insular region belonging to the salience network received signals from the lateral PFC (part of CEN), which allowed discriminating meditators from controls during mindfulness [21]. The right dorsolateral PFC (dlPFC; part of CEN) has been identified as the primary agent involved in the control of episodic retrieval, whereas the left dlPFC has been discovered as one of its key functions in modifying cognitive control functions [22].…”
Section: Discussionmentioning
confidence: 98%
“…Many previous studies have shown a relationship between mindfulness scores and functional connectivity of the lCEN and salience network, but not the rCEN [19,20]. A more recent study demonstrated that the insular region belonging to the salience network received signals from the lateral PFC (part of CEN), which allowed discriminating meditators from controls during mindfulness [21]. The right dorsolateral PFC (dlPFC; part of CEN) has been identified as the primary agent involved in the control of episodic retrieval, whereas the left dlPFC has been discovered as one of its key functions in modifying cognitive control functions [22].…”
Section: Discussionmentioning
confidence: 98%